Preserving and Retrieving Health Records using Conjunctive Keyword Search with Designated Tester and Timing Enabled Proxy Re-Encryption in Cloud - Sushma, SA; Shubha, C; Asha, K (International Journal of Computer Sciences and Engineering, 2018)
Electronic health records(EHR’s) allows the patient to create his own health information in a hospital and share the information with other doctors in other hospitals.EHR provides security to the personal information of users. For providing privacy and security to EHR’s we use SE(Searchable Encryption) which is a cryptographic technique that allows the user to search for a specific information in encrypted content. In this paper we have used conjunctive keyword search with designated tester and timer enabled proxy re-encryption function which is a time dependent SE scheme. Public key encryption with keyword search (PECK) allows the user to search on encrypted data without decrypting it. Sometimes the patient may want to provide access rights to others , it may be his doctor without revealing his private key. This can be accomplished using proxy re-encryption(PRE). Patients can provide partial access rights to others in a limited time period to perform search operations. The amount of time the third party can search and decrypt the encrypted documents can be controlled. The access rights can be revoked back when the time period expires. This prevents re-encryption of the entire document and generation of keys. A time server is used in the system to generate time tokens for users.